Associations of visit-to-visit variabilities and trajectories of serum lipids with the future probability of type 2 diabetes mellitus - Qian Sun (BMC, 2021)
Abstract Background Serum lipid abnormalities are generally considered as a major risk factor for type 2 diabetes mellitus (T2DM). However, evidence for the effect of long-term serum lipid fluctuations on future T2DM probability remains limited. Methods A total of 4475 nondiabetic participants who underwent annual health examinations between 2010 and 2013 were followed for the subsequent 5-year risk of T2DM. The Cox proportional hazards model was performed to evaluate the associations of visit-to-visit variabilities and trajectories of triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-c) and low-density lipoprotein cholesterol (LDL-c) with T2DM probability. Results During the five-year follow-up, 223 newly developed T2DM cases were identified. Compared with the “Low” TG trajectory, “Moderate” and “Moderate-High” TG trajectories were significantly associated with T2DM incidence, with adjusted hazard ratios (HRs) and 95 % confidence intervals (CIs) of 1.51 (1.12-2.03) and 2.55 (1.62-4.03), respectively. Additionally, participants in the third and fourth quartiles of TG/standard deviation (SD) were associated with increased T2DM probability when compared with those in the lowest quartile. After excluding individuals with prediabetes, participants with “Moderate-High” TG trajectory still had a 2.43-fold greater risk of T2DM compared with those with “Low” TG trajectory (95 % CI: 1.28-4.63). In addition, compared with participants in “Low” HDL-c trajectory, the future T2DM probability was significantly reduced in those with “Moderate” and “High” HDL-c trajectories, with HR (95 % CI) of 0.52 (0.37-0.72) and 0.38 (0.18-0.80), respectively. After excluding individuals with prediabetes, the “Moderate” HDL-c trajectory remained associated with decreased T2DM probability when compared with “Low” HDL-c trajectory (HR: 0.55, 95 % CI: 0.35-0.88). However, the incidence of T2DM was not associated with the long-term fluctuations of TC and LDL-c. Conclusions Long-term visit-to-visit variability of TG, and the change trajectories of TG and HDL-c were significantly associated with future T2DM probability. Moreover, these associations were not affected after excluding individuals with prediabetes.